Поняття стресу та психологічної стійкості в межах різних теоретичних підходів - Кравцов, Д. Р.; Kravtsov, D. R. (Габітус. - 2020. - Вип. 18, т. 1. - С. 112-116, 2020)
Досліджено поняття стресу та історію його виникнення. Визначено теоретичні напрями дослідження адаптації особистості до впливу стрес-факторів. Розглянуто основні термінологічні поняття психологічної стійкості, які були визначені як проблеми психологічної адаптації людини, емоційної стійкості, особлива взаємодія компонентів психічної діяльності, а саме емоційних.

In modern society, the impact on the personality of various stressors is increasing, namely: the accelerated pace of life of megacities, increasing the volume and quality of information received, changes in social life, deteriorating environmental conditions and the impact of many other stressors. The modern era is characterized by a constant increase in the load on the human psyche and nervous system. The economic crisis, falling living standards, rising prices, instability in the political situation, and more, are leading to rising social tensions. Modern people live in a state of constant stress on her body. A certain problem is that stress is unjustifiably separated from such concepts as “tension”, “pressure”, “requirements” and “stressors”. Sometimes the term “stress” can be used as a synonym for a special kind of pressure, which leads to the view that stress can be positive. The ambiguity of the interpretation of the concept of “stress”, the burden of its medical-biological and one-sided psychological ideas, has led to the fact that some authors, especially domestic works, prefer the concept – “mental tension”. Psychological stress as a special mental state is a kind of reflection of the subject of a complex, extreme situation in which he is. Numerous foreign and domestic scientific studies show the negative impact of stress on human health in the twenty-first century. This raises the urgent problem of preserving the health of the nation. A person with a stable psyche performs his social roles well, makes his social and professional contribution to society, constantly improves himself and harmonizes his interaction with the outside world. But in order to consider the impact of stress on the human body, we must first consider the psychological stability of man in different theoretical approaches. In the offered article the basic terminological concepts of psychological stability which have been defined as a problem of psychological adaptation of the person, emotional stability, special interaction of components of mental activity, namely emotional, etc. are considered.

Исследованы понятие стресса и история его возникновения. Определены теоретические направления исследования адаптации личности к влиянию стресс-факторов. Рассмотрены основные терминологические понятия психологической стойкости, которые были определены как проблемы психологической адаптации человека, эмоциональной стойкости, особое взаимодействие компонентов психической деятельности, а именно эмоциональных.
The concept of stress and psychological resistance within the limits of different theoretical approaches
Кравцов, Д. Р. Поняття стресу та психологічної стійкості в межах різних теоретичних підходів / Кравцов Д. Р. // Габітус. - 2020. - Вип. 18, т. 1. - С. 112-116. - DOI: https://doi.org/10.32843/2663- 5208.2020.18.1.20.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; стрес; stress; стресс; психологічна стійкість; psychological stability; психологическая стойкость; стресостійкість; stress resistance; стрессоустойчивость; погляди вчених; views of scientists; взгляды ученых